ANALYSIS OF PHONOLOGICAL ERRORS IN THE SHORT STORY ANGSA PUTIH WAS NOT ALWAYS WHITE BY STUDENTS OF SMAN 10 TASIKMALAYA - Ahmad Taufik; Winda Murni; Hilwa Hamya Aulia; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
This research aims to analyze phonological language errors in the short story